2017
DOI: 10.7717/peerj.3431
|View full text |Cite
|
Sign up to set email alerts
|

Detection and drug resistance profile of Escherichia coli from subclinical mastitis cows and water supply in dairy farms in Saraburi Province, Thailand

Abstract: Subclinical mastitis is a persistent problem in dairy farms worldwide. Environmental Escherichia coli is the bacterium predominantly responsible for this condition. In Thailand, subclinical mastitis in dairy cows is usually treated with various antibiotics, which could lead to antibiotic resistance in bacteria. E. coli is also a reservoir of many antibiotic resistance genes, which can be conveyed to other bacteria. In this study, the presence of E. coli in milk and water samples was reported, among which enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 36 publications
4
36
1
2
Order By: Relevance
“…This indicated a wide diversity of resistance which might persist in the environment and proliferate, thus creating great chances for the spread of resistance genes via horizontal or lateral gene transfer causing negative influences on human and animal antibiotic chemotherapy [60]. The findings corroborate those of Hinthong et al [61] where 21 antibiotic-resistance patterns were elucidated. However, the overall predominant phenotypes were AP-A-GM-E-AUG, A-E-AP and A-E-TS added to C-T-E resistance patterns observed in Salmonella and E. coli species, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…This indicated a wide diversity of resistance which might persist in the environment and proliferate, thus creating great chances for the spread of resistance genes via horizontal or lateral gene transfer causing negative influences on human and animal antibiotic chemotherapy [60]. The findings corroborate those of Hinthong et al [61] where 21 antibiotic-resistance patterns were elucidated. However, the overall predominant phenotypes were AP-A-GM-E-AUG, A-E-AP and A-E-TS added to C-T-E resistance patterns observed in Salmonella and E. coli species, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, isolates harboring bla CMY2 were in almost all cases, AM-resistant and FOX-susceptible or even susceptible to all blactams tested. Hinthong et al 28 detected isolates displaying the same characteristic among nonpathogenic E. coli from a water supply in Thailand. Davis et al 29 demonstrated that in the absence of a selective pressure, which can be observed in natural settings, where antibiotic presence is limited, microorganisms are more prone to accumulate mutations leading to dysfunctional pseudogenes (also antibiotic resistance pseudogene), which lost their ability to be expressed.…”
Section: Discussionmentioning
confidence: 98%
“…There is ample evidence that the widespread use of antibiotics in agriculture and medicine is the main reason for the high resistance rate of Gram-negative bacteria (Bothyna & Randa, 2018). Various food and environmental sources contain bacteria resistant to one or more antimicrobial agents used in human or veterinary medicine and animal food production (Hinthong, Pumipuntu, & Santajit, 2017).…”
Section: E Coli Isolated From Retail Foodsmentioning
confidence: 99%